Estrutura e Função Testiculares em Roedores Silvestres das Famílias Echimyidae (Trinomys moojeni) e Cricetidae (Akodon cursor, Akodon montensis, Necromys lasiurus e Oligoryzomys migripes), da Reserva Particular do Patrimônio Natural do Caraça - MG - Dirceu Antonio Cordeiro Junior (2009)
The spiny rat (Trinomys moojeni) is a rodent found in the Atlantic forest, which is considered one of the most diverse and threatened biomes in the world. Knowledge on reproductive biology and physiology is critical to conservation and species management, allowing the prevention of extinction and the use of males in natural and artificial reproduction programs. The main objectives of the present study were to investigate the testis structure as well as spermatogenic and Sertoli cell efficiency in the spiny rat captured in the Caraça Natural Reserve, a fragment of the Atlantic Rainforest located in the State of Minas Gerais, Brazil. Ten sexually mature spiny rats were analyzed. Intraperitoneal injections of tritiated thymidine were administered in order to estimate the duration of spermatogenesis. The testes were perfused-fixed in buffered glutaraldehyde and routinely processed for histological and morphometric analyses as well as the characterization of the stage of seminifeous epithelium cycle. Volume density (%) of seminiferous tubules and Leydig cells were 97 ± 0.3 and 0.3 ± 0.02, respectively. The duration of one spermatogenic cycle and total duration of spermatogenesis were 8.6 ± 0.1 and 38.5 ± 0.5 days, respectively. Due to the very high volume density of the seminiferous tubules, short duration of spermatogenesis, tubule length per gram of testis (~40 meters), high Sertoli cell efficiency (~15 spermatids per Sertoli cell) and high number of Sertoli cells per testis gram (53 million), spermatogenic efficiency in the spiny rat (82 million) is by far the highest of the mammalian species investigated thus far. Key-words: Spiny rat (T. moojeni); testis; spermatogenic cycle length; Sertoli cells; Leydig cells; spermatogenic efficiency.